The AWK programming language - Aho, Alfred V.; Kernighan, Brian W.; Weinberger, Peter J. (Addison-Wesley professional computing series., 2024)
Awk was developed in 1977 at Bell Labs, and it’s still a remarkably useful tool for solving a wide variety of problems quickly and efficiently. In this update of the classic Awk book, the creators of the language show you what Awk can do and teach you how to use it effectively.